PENGUKURAN KINERJA DENGAN PRINSIP VALUE FOR MONEY PEMERINTAH KOTA BATU - Andriani, Sri (EL MUHASABA: Jurnal Akuntansi (e-Journal), 2012)
This research is to measure the service has been conducted by the government of Batu City using two data analysis, are monetary performance ratio and value for money. The performance of Batu government measured using value for money classified into three those are: economy, efficienty, and effectiveness. The performance of Batu government in economy based on how to realize the fund, the performance of Batu government in efficienty based on the reality of credit (the  outcome) of fund is higher than the debet (income) and based on the effectiveness because realization of revenue greater than budget revenue. The performance of Batu government measured using monetary performance ratio classified into five: effetiveness, efficiency, independence, activity and Debt Service Coverage Ratio (DSCR). The performance of Batu government is less effective in realizing the income, however the goverment is efficient enough,  thought it has been inreasing in 2009. Batu government has been independence, because it could decrease and keep in depending toward external side (exspecially toward central and province government), Batu government measured using activity ratio, most of the fund is given  to local apparatus needs, so the expense of public service toward local expense fund is relatively small, and based on DSCR Batu government is good.